Abdominal attack in a patient with hereditary angioedema due to C1 inhibitor deficiency complicated by a perforated peptic ulcer - Obtulowicz, Piotr; Stobiecki, Marcin; Dyga, Wojciech; Popiela, Tadeusz; Obtulowicz, Krystyna (Alergologia Polska - Polish Journal of Allergology, 2024)
A 30-year-old male with hereditary angioedema (HAE) due to C1 inhibitor deficiency was admitted to the Emergency Department (ED) due to severe abdominal pain lasting for 3 hs with severe bloating and weakness. pdC1INH and fluids were applied as usual and the patient was discharged with feeling better. A few hours later abdominal symptoms recurred and erythema appeared, thus the allergy to antispasmodic drug taken by the patient was suspected. In the ED, the patient received anti-allergic treatment and was discharged again. After 3 h severe abdominal symptoms returned with fever. The patient was readmitted to the ED with peritoneal symptoms. Abdominal X-ray confirmed digestive tract perforation. Laparotomy revealed perforation of the chronic duodenal ulcer. In conclusion, we indicate that a HAE patient with an abdominal pain not resolving after usually effective treatment, should be hospitalized and monitored. Differential diagnosis of reasons other than HAE attack should be made.